Study of Ratio of Pineapple and Water Spinach with Arabic Gum Concentration on The Quality of Fruit Leather - Suchi Andriani Maqfirah Lubis; Herla Rusmarilin; Terip Karo-Karo (Universitas Sumatera Utara, 2014)
The aim of this research was to find the effect of ratio pineapple pulps and water spinach with several arabic gum concentration on the quality of pineapple and water spinach mixture fruit leather. This research was conducted by using completely randomized design with two factors, i.e. :ratio of pineapple and water spinachpulps (%) (P) : (70:30 ; 60:40 ; 50:50 ; 40%:60% ; 30:70) and arabic gum concentration (%) (K): (1,1, 1,2 and 1,3). Parameters analyzed were moisture content, ash content, vitamin C content, crude fiber content, total soluble solid, total acid, score organoleptic values of colour, taste and texture and hedonic organoleptic values of colour, taste, flavour and texture. The results showed that theratio of pineapple and water spinach pulps had highly significant effect on moisture, ash, vitamin C, crude fiber, total soluble solid, total acid, score organoleptic values of colour, taste and texture, and hedonic organoleptic values of colour, flavor, taste and texture. Arabic gum concentration had highly significant effect on on moisture, ash, vitamin C, crude fiber, total soluble solid, total acid, and had no significant effect on organoleptic score of colour, taste and texture, and hedonic organoleptic values of texture. Interactions of the two factors had highly significant effect on total solubility solid and had no significant effect on moisture, ash, vitamin C, crude fiber, total acid, score organoleptic score of colour, taste and texture, and hedonic organoleptic values of colour, flavor, taste and texture. The ratio of pineapple and water spinach pulps of (70% : 30%) and Arabic gum concentration of (1,3%) produced the best quality of fruit leather and more acceptable. Keywords: Arabic gum, Fruit leather, Pineapple, Water Spinach